Девушка на скале: [повести : перевод с английского] / Джеймс Кервуд - Кервуд Джеймс Оливер (ТДЛ, 2014)
Экземпляры: аб. (20180411) / Инвентарный номер: 58227 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 36 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44